Pemanfaatan Digital Marketing dengan Foto Produk dan Desain Sosial Media - Fenilinas Adi Artanto; Mochamad Nasir (Yayasan Literasi Sains Indonesia, 2024)
Efforts have been made to improve the quality of education at Vocational High Schools (SMK) with the teaching factory program (TEFA), which is a production or service-based learning method in accordance with current industry standards. One of the needs of Vocational Schools in an effort to support TEFA activities is digital marketing training using digital marketing methods in accordance with the marketing vocations found in Vocational Schools. This activity is designed to train PGRI Batang Vocational School students in product photography techniques and social media design using Canva. Activities are carried out in three stages, namely preparation, training and evaluation. The training includes an introduction to digital marketing concepts, basic photography techniques (lighting, composition, and exposure triangle), as well as social media content design using product photos. As a result, the participants were able to create product photos and design interesting social media content. One of the outcomes of this activity is the Instagram account @unique_clotes. since3202 which has been used to market TEFA products. The evaluation stage shows that this activity can provide digital marketing capabilities that can only be done with a simple tool in the form of a smartphone, so that it can support TEFA activities.